Intraoperative endoscopy-assisted tumor debulking in pediatric peutz-jeghers syndrome with early onset massive polyp burden phenotype - Maria E. Tecos; Matthew Ballweg; Andrew Huang-Pacheco; Angela Hanna; Abdalla Zarroug; Patrick Thomas (Elsevier, 2022)
Peutz-Jeghers Syndrome is an autosomal dominant disorder linked to abnormalities in STK11, and is associated with mucocutaneous pigmentation, sex cord tumors, and gastrointestinal polyps. While it is extremely rare in children under the age of 2, several cases of profound disease have been documented in this population. Here, we detail a case of Peutz-Jeghers Syndrome presenting initially as intussusception, where massive polyp burden nearly occluded the duodenum of a 15-month-old patient and required multimodal operative intervention. Further, we posit that race-based implicit bias may contribute to delays in care and the identification of patients at risk for rare diseases, particularly with atypical presentation, such as the child highlighted in this case.